Quality Profile and Antioxidant Activity of Milkfish (Chanos chanos) Sausage with the Addition of Red Bean Flour (Phaseolus vulgaris L.) - Kumalasari, Ika Dyah; Melati, Aprillia Rizki (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2025)
Red bean are renowned for high antioxidant capable of preventing the Reactive Oxygen Species (ROS) formation that triggers the formation of free radicals. Meanwhile, milkfish (Chanos chanos) has a high protein content and low fat compared to other brackish water fish. Therefore, this study aimed to determine the chemical quality, microbial, and sensory acceptance of milkfish sausage with red bean flour. A completely randomized design (CRD) was used with one treatment factor namely variations in the ratio of milkfish to red bean flour at F0 (100%:0), F1 (75%:25%), F2 (50%:50%), and F3 (25%:75%). Parameters analyzed include moisture, ash, fat, total protein, carbohydrate, dietary fiber, antioxidant, microbiological total plate count (TPC), as well as organoleptic features namely color, taste, aroma, texture, and elasticity. Data were analyzed using SPSS version 23.0 which was tested with One Way ANOVA followed by Duncan Multiple Range Test (DMRT) at the 5% significance level when significant differences were found. The results showed that red bean flour in milkfish sausage had a significant effect on all treatments. The higher the amount of red bean flour added, the greater the value of ash, carbohydrate, and dietary fiber content, while the value of water, fat, protein, and TPC decreased. The strongest antioxidant activity indicated by IC50 was found in F3 at 83.21 ppm. TPC testing showed that all formulations meet the quality requirements of SNI fish sausage. The level of consumer acceptance significantly influenced the acceptance of color, taste, texture, chewiness, aftertaste, and overall. Milkfish sausage added with red bean flour had good chemical quality, microbial, and antioxidant activity.